Myocardial infarction with non-obstructive coronary arteries (MINOCA) - Yildiz, Mehmet; Ashokprabhu, Namrita; Shewale, Aarushi; Pico, Madison; Henry, Timothy D.; Quesada, Odayme (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction with non-obstructive coronary arteries (MINOCA) is evident in up to 15% of all acute myocardial infarctions (AMI) and disproportionally affects females. Despite younger age, female predominance, and fewer cardiovascular risk factors, MINOCA patients have a worse prognosis than patients without cardiovascular disease and a similar prognosis compared to patients with MI and obstructive coronary artery disease (CAD). MINOCA is a syndrome with a broad differential diagnosis that includes both ischemic [coronary artery plaque disruption, coronary vasospasm, coronary microvascular dysfunction, spontaneous coronary artery dissection (SCAD), and coronary embolism/thrombosis] and non-ischemic mechanisms (Takotsubo cardiomyopathy, myocarditis, and non-ischemic cardiomyopathy)—the latter called MINOCA mimickers. Therefore, a standardized approach that includes multimodality imaging, such as coronary intravascular imaging, cardiac magnetic resonance, and in selected cases, coronary reactivity testing, including provocation testing for coronary vasospasm, is necessary to determine underlying etiology and direct treatment. Herein, we review the prevalence, characteristics, prognosis, diagnosis, and treatment of MINOCA -a syndrome often overlooked.